IDENTIFIKASI MORFOLOGI KAWASAN KAMPUNG MELAYU KOTA SEMARANG - Wahjoe Rini; Rizqy Ridho (Universitas Islam Sultan Agung Semarang, 2021)
ABSTRACTCity development increases with the increase in the number of people living in a city. Urban development as a result of development has created metropolitan cities as centers of growth that drive the urbanization process. The spatial component is not only the background of the inhabitants, but also the physical buildings which become assets to maintain the existence of the village. This is supported by the Trancik theory which states that the physical space theory of cities consists of basic images, linkages, places, and these three theories are complementary. In addition to the morphological theory according to Trancik, to determine physical specifications that are supported by morphology theory which contains the architectural form of an area. By developing cities, urban morphology will also change according to city developments. The process of forming urban morphology is the process of forming city life. An ancient village that still has high historical value and has an important meaning, namely Kampung Melayu. The potential for cultural and ethnic images that have more than one ethnicity makes Kampung Melayu a role in ordering morphology in the city of Semarang. The research objective is to identify the morphology of the Kampung Melayu Semarang. The method used is descriptive qualitative analysis with primary data in the form of observation and secondary data in the form of literature review. The resulting output is the morphology of Kampung Melayu seen from the theory of Ground, Linkage and Place drawings as well as road patterns so that later it can be used to determine the Spatial Plan.Keyword: Morphology, City Development, Kampung Melayu ABSTRAKPerkembangan kota ditandai dengan bertambahnya jumlah penduduk yang tinggal di suatu kota. Pembangunan perkotaan dari hasil pembangunan selama ini telah menciptakan kota-kota metropolitan sebagai pusat pertumbuhan yang mendorong proses urbanisasi. Komponen ruang bukan hanya hanya latar belakang penduduknya, namun juga bangunan fisik yang menjadi aset untuk mempertahankan eksistensi kampung. Hal ini didukung dengan teori Trancik yang mengatakan bahwa teori ruang fisik kota terdiri dari figure ground, linkage, place dan ketiga teori ini saling melengkapi. Selain teori morfologi menurut Trancik, untuk menentukan identifikasi fisik didukung dengan teori tipomorfologi yang berisi mengenai bentuk arsitektur suatu kawasan.Dengan berkembangnya kota maka morfologi perkotaan juga akanberubah mengikuti perkembangan kota. Proses terbentuknya morfologi kota (urban morphology) merupakan proses terbentuknya kehidupan kota. Potensi citra budaya serta memiliki etnis lebih dari satu menjadikan Kampung Melayu memberikan peran dalam pembentukan morfologi di Kota Semarang. Tujuan dilakukannya penelitian yaitu untuk mengidentifikasi Morfologi kampung Melayu Semarang. Metode penelitian yang digunakan yaitu analisis deskriptif kualitatif dengan pengumpulan data primer berupa observasi lapangan dan data sekunder berupa kajian literatur. Keluaran yang dihasilkan yaitu berupa morfologi Kampung Melayu dilihat dari teori Figure Ground, Linkage dan Place serta pola jalan sehingga nantinya dapat digunakan untuk arahan dalam menentukan Rencana Tata Ruang.Keyword: Morfologi Kota, Perkembangan, Kampung Melayu